Comparative Analysis of the Impact of Advanced Information Technologies on the International Real Estate Market - Yang, Jingwen (Transactions on Economics, Business and Management Research, 2024)
This study examines the impact of advanced information technologies, such as big data, the Internet of Things (IoT), and artificial intelligence (AI), on the global real estate market. Through comparative analysis of real estate markets in North America, Europe, and Asia, and specific case studies from the US, UK, and China, we quantified the effectiveness of these technologies from 2018 to 2023. Our findings show that big data analytics improved market forecasting accuracy by 15.2%, IoT in smart buildings reduced energy consumption by 10.3% and enhanced security by 17.5%, and AI in property management increased operational efficiency by 17.6% and reduced maintenance costs by 13.2%. North America showed the highest technology acceptance, with a 20%-30% improvement in market efficiency, followed by Europe at 15%-25%, and Asia at 10%-20%. The successful application of these technologies depends on policy environment, market acceptance, and enterprise management. This research offers valuable insights and quantitative evidence for policymakers, industry practitioners, and researchers, highlighting the need for future studies on the integrated effects and long-term impacts of technology convergence.